Molecular Mechanism of Nano-Hydroxyapatite Surface Changes from Hydrophilic to Hydrophobic - Ran, Xu; Yu, Xueying; He, Jin; Xiao, Zhe (Asian Journal of Chemistry, 2014)
The hydroxyapatite was modified via a stearic acid with different content. The microstructure, surface structure and surface element binding energy of the modified hydroxyapatite were investigated. Furthermore, the activation ratio of the modified hydroxyapatite was also tested. The FTIR and XPS detection revealed that the stearic acid molecules had been grafted onto the hydroxyapatite’s surface through ionic bonds, which had been formed through a reaction between the carboxyl groups of the stearic acid molecules and the calcium ions on the hydroxyapatite’s surface. The result of the activation ratio test demonstrated that in the presence of a critical value of stearic acid, the hydroxyapatite’s surface was then modified to a nearly complete hydrophobic state.